EFEKTIVITAS PENGENDALIAN INTERNAL ATAS PELAKSANAAN PAYMENT POINT ONLINE BANK (PPOB) PADA PT. PLN (PERSERO) AREA MALANG - AKHYANI, NUR RABBIYAH (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research was conducted to understand the application of the internal control system implementation for the Online Bank Payment Point (PPOB) at PT. PLN (Persero) for the Malang area and the extent of the effectiveness of internal control for the Online Bank Payment Point (PPOB) at PT. PLN (Persero) for the Malang area. This research is a qualitative descriptive research, taking place at PT. PLN (Persero) of the Service and Network Area (APJ) of Malang with data sources in theform of interviews, analyzed using the internal control theory of Bodnar and Hopwood (2004). The results of the research showed that the implementation of the internal control system for the Online Bank Payment Point (PPOB) at PT. PLN (Persero) for the Malang area has been good. This was indicated by the presence of a system that is clear about the distribution of duties and authorities among DPP-UPI, PT PLN, the Switching Company, and Collecting or Banking, and it can be said to beeffective because the control environment has implemented the six foundations of PT PLN Management, including adequate risk assessment with strong paying laws, control activities conducted synergistically between organizational institutions, information and socialization supported by good tools, and good monitoring or oversight.Keywords: Internal Control, PLN, PPOB